2005
DOI: 10.1002/pst.188
|View full text |Cite
|
Sign up to set email alerts
|

Multiple imputation compared with restricted pseudo‐likelihood and generalized estimating equations for analysis of binary repeated measures in clinical studies

Abstract: Non-likelihood-based methods for repeated measures analysis of binary data in clinical trials can result in biased estimates of treatment effects and associated standard errors when the dropout process is not completely at random. We tested the utility of a multiple imputation approach in reducing these biases. Simulations were used to compare performance of multiple imputation with generalized estimating equations and restricted pseudo-likelihood in five representative clinical trial profiles for estimating (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…The MI specification of this study is described as follows: due to the large portion of missing values, the MI specification included 50 imputations, which is reported to produce consistent parameter estimates in direction and magnitude (Horton & Lipsit, 2001) and is often used in many studies with large datasets (e.g., (Kamakura & Wedel, 2000) and (Lipkovich, Duan, & Ahmed, 2005). All study variables were entered in the imputation process to maximize all of the covariate information.…”
Section: -2: Checking Missing Patternsmentioning
confidence: 99%
“…The MI specification of this study is described as follows: due to the large portion of missing values, the MI specification included 50 imputations, which is reported to produce consistent parameter estimates in direction and magnitude (Horton & Lipsit, 2001) and is often used in many studies with large datasets (e.g., (Kamakura & Wedel, 2000) and (Lipkovich, Duan, & Ahmed, 2005). All study variables were entered in the imputation process to maximize all of the covariate information.…”
Section: -2: Checking Missing Patternsmentioning
confidence: 99%
“…In future research we intend to apply our suggested missing imputation technique to repeated models using generalized estimation equations. 44,45 Our study demonstrated a successful application of statistical theory in imputing missing data to psychophysiology research. Psychiatrists and clinicians should find the suggested method accessible and useful for attaining meaningful conclusions when some data are missing.…”
Section: Discussionmentioning
confidence: 84%
“…Our model (Equation 1) based on the literature in psychophysiology did not account for the repeated measure structure of the heart rate data with a possible inflation of standard errors, in other words, deflation of P ‐values. In future research we intend to apply our suggested missing imputation technique to repeated models using generalized estimation equations 44,45 …”
Section: Discussionmentioning
confidence: 99%
“…Likelihood‐based methods, such as mixed models for repeated measures (MMRM), do not generate explicit predictions of unobserved outcomes but model them implicitly through estimated within‐subject correlations between time points. The MMRM approach is commonly used for continuous outcomes, whereas generalized linear mixed models (GLMM) can be used for binary endpoints . For continuous outcomes, MMRM is easy to implement and typically yields efficient and consistent estimates.…”
Section: Choice Of Estimands In Long‐term Studiesmentioning
confidence: 99%
“…The MMRM approach is commonly used for continuous outcomes, 18 whereas generalized linear mixed models (GLMM) can be used for binary endpoints. 19 For continuous outcomes, MMRM is easy to implement and typically yields efficient and consistent estimates.…”
Section: Analysis Considerationsmentioning
confidence: 99%